PREGNANCY IN WOMАN ON DIAL YSIS - T. V. Bondarenko; L. Y. Morgunov (Исследования и практика в медицине)
End-stage of chronic kidney disease adversely affects fetal and maternal outcomes during pregnancy. The last few years, advances in our knowledge about the interaction of pregnancy and renal function resulted in the improvement of fetal outcome in patients with chronic renal failure and also in the management of pregnant women with end-stage renal disease maintained on dialysis.